Challenges facing the asean political and security community due to the 2021 Myanmar military coup: the role of asean centrality - Anik Yuniarti, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The coup in Myanmar in February 2021 marked a significant escalation in the country’s domestic issues. It presented a considerable challenge for the ASEAN Political and Security Community (APSC), which aims to foster political and security cooperation to achieve stability and peace among ASEAN member states. Members of the ASEAN Community are committed to upholding democratic principles and human rights. Additionally, ASEAN countries have agreed to prioritise ASEAN centrality in decision-making processes to address regional challenges. This study discusses how the 2021 military coup in Myanmar has challenged the ASEAN Political and Security Community. The inability to resolve this coup highlights the limitations of ASEAN centrality. The coup exposes ASEAN’s lack of a coercive mechanism to address violations of democracy and human rights by the Myanmar military regime. Furthermore, the absence of unity among ASEAN members in responding to the situation in Myanmar and actions that deviate from ASEAN agreements have undermined the organisation’s credibility and cohesion, raising increasing concerns.